Soil fertility - Foth, Henry D. (Lewis Publishers, 1997)
Soils are one of the world's most important resources, and their protection, maintenance, and improvement is critical to the continuance of life on earth. Soil Fertility, Second Edition, offers thorough coverage of the fertility, composition, properties, and management of soils. This book carries on the tradition of excellence established by authors Henry Foth and Boyd Ellis, leading soil scientists whose previous books in this field have become multi-edition classics.The Second Edition of Soil Fertility has been significantly expanded to include more information on mineralogy, while keeping the thorough coverage of essential topics. The book presents soils as dynamic, constantly changing bodies, and relates soil fertility and management to the mineralogy of their origin. Four new chapters offer updated information on soil charge properties, ion adsorption, exchange and fixation, and soil reaction. There is also a far greater emphasis on environmental issues, reflecting the increasing importance of environmental concerns to agronomists and soil scientists today